Pendidikan Anti Korupsi dalam Perspektif Islam - Kurniawan, Ade (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
Corruption always has a negative impact on the life of the nation and state. This dishonorable behavior has hurt the people's justice. Deviations on the basis of corruption have reduced the quality of the country to the community. Therefore it is necessary for the awareness of the whole community to participate in efforts to eradicate, eliminate, and minimize so that corruption can be prevented. The spirit of anti-corruption needs to be introduced to all levels of society, especially in the world of education, anti-corruption education is part of moral education in the perspective of Islamic religious education. Corruption is synonymous with, not trustful, dishonest and not grateful for all the blessings given by Allah Almighty and always feel lacking. Anti-corruption education is part of moral education in the perspective of Islamic religious education, where the source is from the Qur'an and hasis, which are expected to be able to manifest and develop virtue values in the younger generation, such as trustworthiness, responsibility, giving thanks to Allah's giving Almighty and honest as a form of piety and faith in Allah.